Molecular epidemiology of syphilis in Scotland. Issue 6 (3rd June 2009) - Cole, M J; Chisholm, S A; Palmer, H M; Wallace, L A; Ison, C A
Abstract : Objective: To examine the molecular epidemiology of syphilis in Scotland. Methods: Ulcer specimens were collected from 85 patients with infectious syphilis. Typing of Treponema pallidum was performed using a method that examines variation in two loci; the number of 60-basepair repeats within the arp gene and sequence variation in the tpr genes. Results: Patients were predominately white men who have sex with men (MSM). Treponemal DNA was detected in 75 specimens and a total of six subtypes were identified from 58 typeable specimens (77%). The most common subtypes were 14 d (44/58, 76%), followed by 14 e (7/58, 12%), 14 j (3/58, 5%), 14 b (2/58, 3%), 14 p and 14 k (1/58, 2%). Conclusions: This study shows that subtype 14 d is the predominant subtype circulating in Scotland and there is a surprising level of genetic diversity within the Scottish MSM community.